The Association between Changes in Interest Rates, Earnings, and Equity Values* - Nissim, Doron; Penman, Stephen H. (Contemporary Accounting Research, 2003)
Numerous studies have documented that stock returns are negatively related to changes in interest rates, but there has been little corroborating research on the information in interest‐rate changes about the fundamentals that the stock market prices. The negative correlation is often attributed to changes in the discount rate, a denominator effect in a valuation model. However, there may also be a numerator effect on the expected payoffs that are discounted. This paper shows that changes in interest rates are positively related to subsequent earnings, but the change in earnings is typically not large enough to cover the change in the required return. Hence, the net (numerator and denominator) effect on equity value is negative, consistent with the results of the research on interest rates and stock returns.